Detection of low-abundance KRAS mutations in colorectal cancer using microfluidic capillary electrophoresis-based restriction fragment length polymorphism method with optimized assay conditions. - Huidan Zhang (Public Library of Science (PLoS), 2013)
Constitutively active KRAS mutations have been found to be involved in various processes of cancer development, and render tumor cells resistant to EGFR-targeted therapies. Mutation detection methods with higher sensitivity will increase the possibility of choosing the correct individual therapy. Here, we established a highly sensitive and efficient microfluidic capillary electrophoresis-based restriction fragment length polymorphism (µCE-based RFLP) platform for low-abundance KRAS genotyping with the combination of µCE and RFLP techniques. By using our self-built sensitive laser induced fluorescence (LIF) detector and a new DNA intercalating dye YOYO-1, the separation conditions of µCE for ΦX174 HaeIII DNA marker were first optimized. Then, a Mav I digested 107-bp KRAS gene fragment was directly introduced into the microfluidic device and analyzed by µCE, in which field amplified sample stacking (FASS) technique was employed to obtain the enrichment of the RFLP digestion products and extremely improved the sensitivity. The accurate analysis of KRAS statuses in HT29, LS174T, CCL187, SW480, Clone A, and CX-1 colorectal cancer (CRC) cell lines by µCE-based RFLP were achieved in 5 min with picoliter-scale sample consumption, and as low as 0.01% of mutant KRAS could be identified from a large excess of wild-type genomic DNA (gDNA). In 98 paraffin-embedded CRC tissues, KRAS codon 12 mutations were discovered in 28 (28.6%), significantly higher than that obtained by direct sequencing (13, 13.3%). Clone sequencing confirmed these results and showed this system could detect at least 0.4% of the mutant KRAS in CRC tissue slides. Compared with direct sequencing, the new finding of the µCE-based RFLP platform was that KRAS mutations in codon 12 were correlated with the patient's age. In conclusion, we established a sensitive, fast, and cost-effective screening method for KRAS mutations, and successfully detected low-abundance KRAS mutations in clinical samples, which will allow provision of more precise individualized cancer therapy.